Conceptual breaches of security and environment in the Anthropocene: the security nexuses in formation since the post cold war: (Tempo e Argumento, 2021)
The Anthropocene model refers to disturbances on the earth's surface caused by intense human activity. Being associated with a new interval in the geological history of the Earth, it has been approached by several areas of knowledge of the so-called Earth sciences, reaching now to the social sciences and humanities, since its implantation. International Relations (IR) seek a better specificity of their functions vis-à-vis the Anthropocene, expanding their field of action. In the field of Security, it is stated that the actors are more connected and committed to each other and that the meaning of Security based on the state actor and in the political and military sectors no longer makes sense in the anthropocentric model and that transdisciplinarity (for the discipline of international relations and beyond) must be affirmed. Collaborating with a manifesto launched at a conference sponsored by the Millennium Journal, of the London School of Economics, we bring the post-Cold War time cut to broaden the socio-environmental debate in transdisciplinary terms to the field of security studies. The Anthropocene foreshadows a time of insecurity. Although attention to security as a threat has grown in the past two decades in a frank stimulus to the post-Cold War debate and securitization is visible in the global system, a large number of security nexuses in transdisciplinary construction persist that deserve critical review in the face of phenomenon of environmental degradation created within the conceptual Anthropocene, which advocates a bipolar human-nature threat